Extracción de nutrimentos en la asociación maíz-frijol con tres especies de malezas - Morales, Leopoldo; Doll, Jerry D. (1975)
Since many farmers in the tropics plant crops in association, a study was conducted to determine the capacity of corn and edible beans (Phaseolus vulgaris) grown alone or in association to extract N, P and K. The effects of three soil types and three weed species on the absorptive capacity of the crops was also studied. The trial was carried out under the controlled conditions of a screenhouse. Plant height, dry weight and the N, P and K content were measured 35 days after planting for all the species. Corn associated with beans grew taller than when grown alone and it also extrated more N, P and K when associated than when grown alone. This is probably due to the nitrogen fixed by the beans which was utilized by the corn, thereby giving it a greater competitive capacity. Pigweed (Amaranthus dubius) was the weed that least competed with corn and beans. Since it is an efficient plant (C4), it seems to be less demanding for N and therefore, did not affect the corn and bean growth during their initial growth period (35 days). In general morning glory (Ipomoea sp.) was more competitive for nutrients with the crops than pigweed or goosegrass (Eleusine Indica). There were significant differences among the nutrient contents of the species between the three soil types. The sandy soil caused the least plant growth.